Kesahan modul kecerdasan emosi kemahiran penyesuaian diri situasi COVID-19 dalam kalangan wanita bekerjaya di Univeriti Malaysia Sabah - Laila Wati Madlan @ Endalan,; Muhamad Idris Bullare@Hj. Bahari,; Chan, Alfred Huan Zhi; NurFarhana Ardilla Aftar,; Norsimah Dasan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The development and testing of the adaptation skills emotional intelligence module was designed to identify the social emotional intelligence scores of female workers at Universiti Malaysia Sabah. This module was built on the component of social emotional intelligence adaptive skills as found in the Bar-On Model. The adaptive components of Bar-On model consist of Reality Testing, Flexibility and Problem Solving. These three components are important for looking at the extent of the efficiency of social emotional intelligence in individuals. Development of the COVID-19 Situational Adaptation Skills Emotional Intelligence Module among Working Women at Universiti Malaysia Sabah is an approach that can be used to train women workers to be flexible in their life and they carrier. The built -in understanding of the effects of the modules used can certainly help working women to adapt to the current situation of the pendemic. This module is an initiative developed specifically to provide space for women to train themselves to deal with situations. The module was developed starting with discussion, draft writing then draft refinement before finally being submitted to an expert for evaluation. The study was conducted using a descriptive design aimed at identifying the level of validity of the construction and testing of the COVID-19 situational adaptation skills emotional intelligence module among female workes at the University Malaysia Sabah. The validity test of the module involved three expert evaluators consisting of lecturers from public universities with qualifications and expertise in psychology and counseling. An expert agree that this module is feasible based on the 87.3% overall validity level. The Cronbach's Alpha value is also high. Therefore, indirectly, this module is suitable to be used to female staff at Universiti Malaysia Sabah. Through an intervention of this module is certainly useful and can be used as a guide when facing similar problems in the future. In fact, it can be used as a basis in drafting (blueprint) programs or activities not only for women employees at UMS but also women in other organizations.